Regulation and Supervision of Halal Prodcuts in Aceh Qanun No. 8/2016 - Friatna, Ida; Abbas, Syahrizal; Wahid, Nazaruddin Abdul (Media Syari'ah, 2024)
Eating and drinking are routine human activities, thus requiring various regulations related to these problems. Allah commands us to eat halal (halalan) and good (thayyiban) food so as not to harm our bodies. Aceh has issued a special regulation to provide protection to the public regarding the products consumed, namely Qanun Number 8 of 2016 concerning the Halal Product Guarantee System, known as Qanun SJPH. This paper wants to find a clear picture of the arrangement and supervision of halal products in Aceh from the Perspective of Qanun Number 8 of 2016 concerning the Halal Product Guarantee System. This research is a qualitative research with a normative juridical approach. All data that has been collected was analyzed using the content analysis method. The result of the research is that the SJPH Qanun has provided a clear description of the guarantee of halal products in Aceh. This regulation of SJPH is a form of responsibility of the Government of Aceh in providing legal protection for Muslims in particular and all Acehnese people in general, regardless of religious origin and certain groups. The main regulatory object is related to halal products, besides that it is also important related to products that meet hygienic standards. Halal product guarantees are regulated in qanuns with a very systematic system of arrangement, supervision and implementation of arrangement and supervision of product distribution in Aceh. The substance of the qanun is very comprehensive regarding guarantees for halal products in the aspects of production, distribution and consumption. Qanun regulates from arrangement, supervision to the provisions of 'uqubat for perpetrators of violations. Arrangement of halal products is carried out starting from raw materials to marketing of halal products, namely products that are labeled halal and/or have received halal certificates from authorized institutions. Furthermore, supervision is carried out from the origin of raw materials, production processes and production facilities on processed animal and/or vegetable products, medicines and cosmetics. The implementation of arrangement and supervision of halal products is the responsibility of LPPOM MPU Aceh and LPPOM can involve an integrated team from cross-agency related to SJPH.